Implementation Of Financial Accounting Standards For Micro, Small, And Medium Enterprises: A Case Study In Batik Jumputan Ibu Sejahtera - Arif Sapta Yuniarto; Siti Hardini (Department of Islamic Economics, Islamic University of Indonesia, 2020)
In Yogyakarta, the Micro, Small, and Medium Enterprises (MSME) have not been able to develop because they cannot access the capital provided by the banks. It happened due to the inability of the MSMEs to prepare the standardized financial reports. This study aimed to determine how to prepare the financial report according to the financial accounting Standards for Mico, Small, and Medium-Sized Entities at Micro, Small, and Medium Enterprises Batik Jumputan Ibu Sejahtera. The study employed the qualitative research method with a descriptive approach. The data analysis included 1) data collection, conducted through an interview, observation, documentation technique, 2) data reduction, 3) data presentation, and 4) conclusion or verification. The data were validated using the triangulation validity technique. The result showed that the financial reports prepared by the MSME Batik Jumputan Ibu Sejahter’s had not followed the Financial Accounting Standards for Micro, Small, and Medium-Sized Entities. The entity’s transaction recording system is less sophisticated, in that it only contains information about cash in and cash out. The managers’ lack of ability and understanding became the key factor influencing the quality of the financial report. After the researcher rearranged the financial statement according to the rules, it was found that the total asset owned by the entity was Rp109,531,936, total liabilities Rp3,160,000, and the total equity Rp106,371,936. The net profit acquired by the entity reached Rp81,083,534. The reports showed that Batik Jumputan Ibu Sejahtera was categorized as a micro-enterprise by the MSME criteria mentioned in the Law of the Republic of Indonesia Number 20 of 2008.